Improvements in the synthesis of highly focused ultrasonic beams using the negative-time part of the 0-order X-wave driving signals. (15th April 2015) - Castellanos, Luis; Ramos, Antonio; Calás, Hector; Bazán, Ivonne
Abstract: The classical 0-order X-wave is a limited-diffraction solution for the scalar wave equation and provides good beam focusing along a large depth, for instance, in high-resolution ultrasonic imaging. In this work, only the negative-time parts of 0-order X-waves are used like driving signals for a Bessel array in order to produce a highly focused acoustic field over a line. This approach maintains the advantages provided by the conventional 0-order X-waves, large depth of focused field with low lateral beam spreading, using only one emission shot. Some achievements obtained by using the proposed technique are a low energy and lower cost to drive the piezoelectric elements while maintaining a similar depth of field and beamwidth as those of the conventional method, a lower space extension of sidelobes, and easier control of the electrical driving system. Theoretical and experimental results support these hypotheses, and confirm the improvements obtained.